Implementation of In-Depth Learning Planning on Zakat Through Discovery Learning with the Assistion of Youtube at Taman Siswa High School - Fadhly Yassin Tanjung; Riyan Vebrianto; Afif Hamzah (LPPPIPublishing, 2026)
This study aims to describe the implementation of In-Depth Learning Planning (IPL) on zakat through the Discovery Learning model, supported by YouTube, in grade 10 of Taman Siswa Senior High School. This study used a descriptive qualitative approach, with data collection techniques consisting of learning observations, analysis of IPL documents and Student Worksheets (LKPD), and analysis of student formative and summative assessment results. Data were analyzed descriptively to illustrate the relationship between planning, implementation, and learning outcomes. The results showed that the implementation of IPL improved students' conceptual understanding and analytical skills in determining the nisab (the threshold limit), calculating zakat levels, and accurately classifying mustahik (the recipients of wealth). Furthermore, students were able to relate the concept of zakat to modern social and economic realities through case analysis activities and zakat calculation simulations. The integration of YouTube into learning also contributed to improving students' digital literacy critically and responsibly, and fostering social empathy for groups in need. Thus, the implementation of IPL based on Discovery Learning is effective in meaningful, contextual zakat learning, oriented toward the development of Higher Order Thinking Skills (HOTS) at the high school level.